A design space for event-centric displays in public libraries - Ducros, Alix; Tabard, Aurélien; Dalsgaard, Peter; Bats, Raphaelle; Eriksson, Eva (Frontiers in Computer Science, 2024)
We present a design space for displays in public libraries; more specifically public displays related to events taking place in the library. The design space is developed from the perspective of the librarians and is intended to support libraries in rethinking, developing, and employing displays to communicate and support the events they host. It is based on a study of 18 concepts co-designed in eight participatory workshops scaling participation to a total of 88 professional librarians. By analyzing the concepts through inductive and iterative analysis, we have defined a design space consisting of 12 aspects, categorized in four themes: interaction-, content-, event-, and display-centric. We argue that the design space can both serve as (1) an analytical tool for understanding and categorizing information displays and identifying overarching design considerations and (2) a generative framework to inspire design across a wide variety of libraries.